A polymethoxyflavone mixture, extracted from orange peels, suppresses the UVB‐induced expression of MMP‐1. (August 2016) - Yoshizaki, Norihiro; Fujii, Takahiro; Hashizume, Ron; Masaki, Hitoshi
Abstract: Ultraviolet (UV) B is the main cause of skin photoageing, which has characteristic features such as deep wrinkles. UVB increases the expression of matrix metalloproteinases (MMPs) in the skin and can cause wrinkles by disrupting components of the extracellular matrix, such as collagen fibres. We now report that a polymethoxyflavone (PMF) mixture, extracted from orange peels, suppresses the UVB‐induced expression of MMP‐1 that involves the inhibition of c‐jun N‐terminal kinase (JNK) activity. Furthermore, the PMF mixture also inhibits the UVB‐induced phosphorylation of JNK. Therefore, the results suggest that the PMF mixture suppresses the UVB‐induced expression of MMP‐1 through the inhibition of JNK phosphorylation and should be useful as an antiphotoageing agent.